‘Whether any material being thinks, or no’: Leibniz’s critique of Locke on superaddition - Lodge, P (Olms, 2016)
Leibniz discusses the relationship between matter and mentality in two places in the New Essays. The first, which features his famous ‘mill argument’, is in the Preface. The second is in Book 4, where Leibniz responds to Locke on the issue of whether we could ever know “whether any material being thinks, or no” (ECHU 4.3.6). The mill argument aims to show that matter conceived as passive extended stuff cannot think through its natural powers. This is something Locke is happy to accept, noting explicitly at ECHU 4.3.6: “matter …is evidently in its own nature void of sense and thought”. However, he considers two additional ways in which matter might be said to think via superaddition at ECHU 4.3.6. I shall be concerned with these here.